Revealing inheritance of white markings in Nili Ravi buffalo - DHANDAPANI, S; VOHRA, VIKAS; MUKESH, M; KUMAR, SANJAY; MEHRARA, K L; SINGH, K P; KUMARI, NAMITA; KATARIA, R S (The Indian Journal of Animal Sciences, 2025)
Among registered Indian buffalo breeds, Nili Ravi is well known for its production potential as well as unique typical five white markings, because of which it is also known as Panch-Kalyani. In this study an attempt was made to understand the inheritance pattern of white markings in 720 progenies sired by 21 bulls and belonging to 381 dams at an organized farm. Based on extent of white markings, animals were classified into typical, under and over white categories and significance of inheritance was tested by Chi- Square, Likelihood ratio and Mc-NemarBowker tests to confirm the results. The results showed distribution of inheritance pattern from sire to progeny, and dam to progeny was that the identical in white markings classes ratios and inheritance of skin/coat colour patterns could not be explained. Further, studies at genomic and epigenetic levels needed to reveal the genetic/methylation differentiation basis of white markings variation in Nili Ravi buffalo.